The Clinical Efficacy and Safety of Nintedanib in the Treatment of Interstitial Lung Disease Among Patients With Systemic Sclerosis: Systematic Review - Khaled S. Al Oweidat; Ahmed A. Abdulelah; Ahmad A. Toubasi; Mohammad Abdulelah; Nour Z. Alatteili; Zaid A. Abdulelah (Canadian Respiratory Journal)
Systemic sclerosis (SSc) is predominantly characterized by an array of cutaneous manifestations including Raynaud’s phenomenon, calcinosis, telangiectasias, and skin fibrosis contributing toward substantial morbidity and diminished quality of life. The monumental impact of the disease regarding mortality is due to its pulmonary involvement known as SSc-associated interstitial lung disease (SSc–ILD). Currently, treatment is chiefly directed toward impeding disease progression with the mainstay treatment approaches involving the utilization of cyclophosphamide, mycophenolate mofetil, rituximab, and tocilizumab. Recently, a tyrosine kinase inhibitor, nintedanib, has been approved for the treatment of SSc–ILD and thus became the first medication to be fully licensed for SSc–ILD. A systematic review based on the Preferred Reporting Items of Systematic Review with Meta-analysis (PRISMA) was conducted after successful registration in PROSPERO to evaluate the efficacy and safety of nintedanib in SSc–ILD. We searched PubMed, Scopus, and CENTRAL up to the first of September 2023 utilizing the following keywords: ((Diffuse Parenchymal Lung Disease) OR (Diffuse Parenchymal Lung Diseases) OR (Interstitial Lung Disease) OR (Interstitial Lung Diseases) OR (Interstitial Pneumonia) OR (Interstitial Pneumonitis) OR (Pulmonary Fibrosis)) AND ((Systemic Scleroderma) OR (Systemic Scleroderma)) AND ((BIBF 1120) OR (BIBF-1120) OR (BIBF1120) OR (Nintedanib esylate) OR (Ofev) OR (Vargatef)). The clinical safety profile of nintedanib was deemed more favorable than other therapeutic regimens currently utilized, in addition to adequate clinical efficacy toward SSc–ILD.